Forecast and clinical-diagnostic significance of increased expression of beta-2microglobulin in the urine in the process of nephropathy formation in essential hypertension - R. L. Kulynych; D. G. Rekalov (Kazimierz Wielki University, 2020)
Introduction. At present, it is obvious that the prognosis for the life of patients with essential hypertension, according to the cardiovascular continuum, is clearly determined primarily by the involvement in the pathological process of target organs and the severity of their structural and functional changes. The aim of the study is to identify the clinical-diagnostic and prognostic value of B2-MGU as a marker of kidney damage in essential hypertension. Materials and methods. To achieve this goal, 46 patients with essential hypertension (45.65% women and 54.35% men) aged from 28 to 71 years (mean age was 51.88 ± 2.17 years), I-II stage of the disease with level of hypertension I-III degree, varying degrees of risk, who did not receive systematic adequate antihypertensive therapy and in which as a result of comprehensive clinical, laboratory and instrumental studies there were no evidence of clinically significant chronic kidney disease. The control group consisted of 17 healthy individuals. Results. In patients with essential hypertension is forming hypertensive nephropathy, which is characterized by statistically significant excessive excretion of beta-2-microglobulin in the urine compared with almost healthy individuals. In patients with increased excretion of beta-2-microglobulin violations of intrarenal hemodynamics were registered significantly more often, violations of functional renal reserve, violations of vascular resistance of renal vessels, in a significantly higher percentage there were pathological changes in circadian rhythm of blood pressure and renal filtration function, the prevalence of concentric and eccentric hypertrophy, proteinuria, which indicates an important clinical, diagnostic and prognostic value of hyper-beta-2-microglobulinuria. Conclusions. The indicator beta-2-microglobulinuria can be used as an adequate marker of hypertensive nephropathy, as having high sensitivity, specificity, positive and negative prognosis.